Analisis Indeks Pencemaran Air Laut dengan Parameter Logam Cu dan Pb di Kawasan Wisata Raja Ampat Papua Barat - Muhammad Taufiq Thahir; Yusnita Lagoa (Jurnal Sumberdaya Akuatik Indopasifik, 2018)
Research has been conducted on the analysis of seawater pollution index in the Raja Ampat tourism park of Papua Barat by using Cu and Pb concentration as parameters. The research aims to produce information on water conditions in Raja Ampat. Those information can ensure the sustainability of this area in the future. AAS (Atomic Absorption Spectrophotometer) instrument was used to perform water samples analysis. Samples taken from five locations, namely Sapokren, Saleo, Waiwo, Waisai Harbour and Waisai Fish Harbour, which were respectively marked with area I, II, III, IV and V. For Cu parameter; area I was found, which was 0.62 mg/L which had exceeded the quality standard, while area II, III, IV, and V were not existed Cu. Furthermore for Pb; the concentration of heavy metals founded in four locations, area I, II, III and IV; 2,99 mg/L, 1,76 mg/L, 1,27 mg/L and 0,23 mg/L respectively. Other while area V was not found Pb concentration. All quality standard data were entered into the pollution index equation in accordance with the guidelines of KepmenLH No. 115 of 2003. The data showed that only one area was still in the good category, area V, the remaining area I, II, III and IV were included in the category of metal contaminated areas of Cu and Pb with varied levels of pollution beginning at low, middle to high.